THE PHONOLOGICAL ILLUSION: THE QUALITY AND NUMBER OF EPENTHETIC VOWELS - Melnik, Gerda Ana (Verbum, 2016)
Adult speakers tend to have difficulties in perceiving non-native sequences of sounds as their perception is influenced by the features of their L1 phonological system. For example, previous studies have shown that Japanese speakers perceptually insert an illusory vowel /u/ in consonant clusters, which are phonotoctically illegal structures in Japanese. While the phenomenon of phonological illusion also occurs in other languages, such as Brazilian Portuguese or Korean, the epenthetic vowels have been shown to be language-specific. Despite these findings, many questions concerning the number of illusory vowels possible in a language and their quality remain open. In this study we will present recent work on the topic and provide a critical comparison of those findings, concentrating on the role of context-sensitivity in the determination of the features of the illusory vowel.